Fractionation of Organic and Inorganic Phosphorus in Sandy Soils irrigated by Treated Wastewater Cultivated by Hordeum vulgre & Vicia faba - Aishah Ramadan Mohamed, Mohamed Ali Elssaidi (Journal of Pure & Applied Sciences, 2019)
Changes in inorganic and organic phosphorus fractions resulting from wastewater application on sandy soil were studied using sequential extraction technique. Plant phosphorus content was determined in a pots study using Hordeum vulgre and Vicia faba. Five levels of wastewater addition, (0, 25, 50, 75 and 100 %) were used for irrigation. Several parameters like pH, EC, CEC, OM and CaCO3 were assessed. The findings showed that wastewater treatments increased the pH, EC, CEC, CaCO3 and OM in treated soil. The highest values recorded with 100% wastewater treatment. Wastewater irrigation influenced soil phosphorus concentrations, the higher values recorded using 100% treatment. Total phosphorus content of the cultivated soil was higher compared to uncultivated soil. Inorganic phosphorus was dominant compound of total phosphorus. Wastewater enhancing organic phosphorus composition of tested soil. The distribution of phosphorus quantities across different fractions (inorganic and organic) in uncultivated soil were Ca-P > Water-P > Organic-P > Read –P >Fe-P > Al-P. While in Vicia faba cultivated soil, were Ca-P > Organic-P > Water-P > Read –P > Fe-P = Al-P. The trend in oil cultivated with Hordeum vulgre were Organic-P > Ca-P > Water-P > Read –P > Fe-P >Al-P. In general, Ca-P is the largest fraction of phosphorus. Which affect phosphorus availability. The Organic-P is important source of phosphorus in soil irrigated with wastewater. Recycling of wastewater enhancing phosphorus concentrations and increasing its content in Hordeum vulgre in comparison with Vicia faba.